Commercial viability vs. social responsibility a study on the best picture awardees of Metro Manila Film Festival from 2003-2007. - Lim, Luisi Jane; Mangubat, Cherry Lyn. (2008.)
This study analyzed the Best Picture awardees of metro Manila Film Festival from 2003-2007 whether they employ more on commercial viability or social responsibility. It aims to identify the films awarded as best picture in the Metro Manila film Festival from 2003-2007; to identify the elements of the film such as its plot, characters, settings, structure, symbolism, and point of view; to analyze the MMFF Best Picture awardees from 2003-2007 level of social responsibility whether it performs its function as a form of mass communication such as surveillance, correlation, transmission of culture, and entertainment; to identify the official gross income of the MMFF Best Picture awardees from 2003-2007 on the final day of showing; and to find out the trends in the movies awarded as Best Picture in the MMFF from 2003-2007 whether it employs more on social responsibility or commercial viability., A self-structured paradigm for the study's theory was devised to incorporate all elements connected in the study which includes the film, the elements of a film, functions of mass communication, and the film's final day of gross receipt. Each of the movies was given its background data. The elements of the film were also identified based on its plot, settings, characters, symbolism, structure, and point of view. an analysis whether each film employs social responsibility was based on the four functions of mass communication which includes surveillance, correlation, transmission of culture, and entertainment. The study shows that the MMFF Best Picture awardees from 2003-2007 are quite socially responsible yet fairly commercially viable. Thus, the said film fest awarded Best Picture films that employ more on social responsibility than commercial viability. The researchers suggest that the moviegoers themselves must be critical in choosing and analyzing a film and must not only depend on the results of the Box office hits. For the future researchers, they may look on the aspect of MMFF's criteria for Best Picture compared to other critically acclaimed international Film Festival.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Metro Manila Film Festival -- 2003-2007.